Beethoven's sonatas woo 47. Their importance in the set of piano sonatas (2017)
The object of study of the present investigation, in this case, the early piano sonatas of Ludwig van Beethoven, as essential pieces in the piano repertoire of the history of academic music. The research topic arises from the recent publication (2007) of the complete set of them, in a critical edition, of the 35 piano sonatas by Professor Barry Cooper, renowned Beethoven specialist. This is the only modern edition that includes, from the beginning, the three WoO 47 sonatas and the next 32 already known. Our review is aimed at gathering information on Beethoven's three WoO 47 Sonatas and the importance of these compositions in the composer's piano repertoire. This article then seeks to show as justifiable the inclusion of these works in the catalog of the complete piano sonatas of the German composer, by collecting sources in this regard and assessing their technical difficulties for the instrument.